EMBODIED MEANING CONSTRUCTION IN EFL LITERARY READING: A READER-RESPONSE STUDY OF THE OLD MAN AND THE SEA - Nur Mutmainna Halim; Abd Halim (English Education Department at FKIP Nommensen University, 2026)
This study investigates how meaning is constructed through embodied cognitive processes when EFL learners engage with The Old Man and the Sea. Grounded in Barsalou’s Embodied Cognition Theory (1999, 2008), which conceptualizes language comprehension as the reactivation of perceptual, motor, bodily, and affective systems rather than abstract symbol manipulation, the study examines reader responses to a literary text characterized by narrative restraint and minimal explicit emotional description. The participants were undergraduate students from the English Literature Study Program at Universitas Negeri Makassar enrolled in the History of English Language and Literature course (2024 cohort). 142 students across five intact classes (A–E), 57 students (40.1%) selected The Old Man and the Sea as their preferred final-test novel and constituted the focal participant group. Data were collected through an open-ended reflective questionnaire eliciting emotional reactions, imagined experiences, reflective pauses, and lingering thoughts after reading. The data were analyzed using thematic analysis with theory-driven coding, guided by embodied cognition categories including sensorimotor imagery, bodily state, action simulation, and affective response. The findings reveal that students consistently relied on embodied simulation to construct meaning, reporting strong experiences of empathy, loneliness, sadness, and admiration derived from imagining Santiago’s physical struggle, pain, fatigue, and isolation. Meaning emerged through experiential inference, as understanding developed from felt bodily and affective engagement rather than explicit textual cues. The study demonstrates the pedagogical potential of literary reading in EFL contexts to foster affective engagement, empathy development, and reader-centred meaning construction, while extending embodied cognition research to authentic classroom-based literary experiences.